2015
DOI: 10.1038/srep14580
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional matrix fiber alignment modulates cell migration and MT1-MMP utility by spatially and temporally directing protrusions

Abstract: Multiple attributes of the three-dimensional (3D) extracellular matrix (ECM) have been independently implicated as regulators of cell motility, including pore size, crosslink density, structural organization, and stiffness. However, these parameters cannot be independently varied within a complex 3D ECM protein network. We present an integrated, quantitative study of these parameters across a broad range of complex matrix configurations using self-assembling 3D collagen and show how each parameter relates to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
204
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(218 citation statements)
references
References 48 publications
(60 reference statements)
10
204
4
Order By: Relevance
“…Cells secrete metalloproteinase enzymes (such as MMPs) to dilute the concentration of collagen and increase the size of the pores to facilitate cell invasion. This effect is more pronounced when the density of the fibers is high and the voids between the fibers are significantly smaller than the cell body (5). Including the effect of the MMPs in our model results in an increase in the cell invasion at higher collagen densities, in agreement with our melanoma observations (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Cells secrete metalloproteinase enzymes (such as MMPs) to dilute the concentration of collagen and increase the size of the pores to facilitate cell invasion. This effect is more pronounced when the density of the fibers is high and the voids between the fibers are significantly smaller than the cell body (5). Including the effect of the MMPs in our model results in an increase in the cell invasion at higher collagen densities, in agreement with our melanoma observations (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the comparison between cell contractility in malignant and normal tissues has shown that the cells with malignant phenotype have a higher level of contractility (1)(2)(3)(4). This elevated contractility is directly proportional to factors such as the stiffness of the extracellular matrix (ECM) and the fiber realignment (5)(6)(7), suggesting that the cross talk between ECM and intracellular contractility mediated by mechanosensory signaling pathways is also implicated in metastasis. Specifically, the activity of Rho, a myosin GTPase that regulates the activity of myosins, is elevated in proportion to the stiffness of the surrounding matrix (1,8,9), and inhibition of Rho-associated protein kinase (ROCK) has been known to reduce the invasiveness of the tumor (1,10), demonstrating that the Rho pathway is a key promoter of cell invasion (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In mesenchymal cells, organization of fibriliar matrices is the major determinant of migration patterns, such that cell migration persistence tends to be highest in aligned matrices [97,[99][100][101]. Both non-malignant and malignant epithelial cells respond to the biomechanics of their surrounding matrix [35], through multiple mechanisms [6,33,35,102].…”
Section: Microstructure Biomechanics and Crosslinkingmentioning
confidence: 99%
“…It is mainly composed by collagen [1] and for this reason, collagen-based networks are widely employed as three-dimensional environments to study cell motility and tumor invasion [2]. Moreover, recent works reflect that the composition and mechanical properties of these threedimensional environments affect cellular phenotypes and migratory patterns [3,4,5].…”
Section: Introductionmentioning
confidence: 99%